the educational parenting Educational Parenting: Meningkatkan Peran Orangtua pada Perkembangan Sosioemosional Anak Usia Dini - Pratisti, Wiwien Dinar (Abdi Psikonomi, 2022)
Early childhood education has a very important role and position in a nation and becomes the basis for the next stage of development. Teachers have a role in children's education at school, and parents are responsible for children's growth and development at home. The problem that often arises is the mismatch between treatment in kindergarten by teachers, and treatment at home by parents, which makes child development less optimal. Educational Parenting program is considered as an effective program in providing understanding to parents about early childhood. Most of them use the lecture method, and it is still rare to use the role-play method as a learning tool for parents to understand early childhood with general material. Therefore, the aim of this study was to examine the effectiveness of educational parenting programs to increase parental understanding of early childhood socio-emotional development. The educational parenting program was held for a day, using 43 parents. The results show that this educational parenting program makes parents more comprehensive in their understanding of early childhood, including chronological age and cognitive, socio-emotional, and psychomotor development. The stimulation that parents can provide in socio-emotional development is in the form of communication skills, introducing emotions, and managing emotions in order to express them more precisely. During this program, parents were enthusiastic and expressed their desire to do parenting programs with the same model again. Thus it can be stated that educational parenting programs with the roleplay method for parents of early childhood can increase parental understanding of early childhood and appropriate stimulation for early childhood socio-emotional development.